2014
DOI: 10.1016/j.rmed.2014.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation effectiveness in smokers with COPD and asthma under real life conditions

Abstract: The results support the view that smokers with respiratory obstructive airway diseases of any severity should be offered an intensive smoking cessation program with regular and long-term follow-up. This will help them to achieve high abstinence rates and prevent relapses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 36 publications
1
11
1
4
Order By: Relevance
“…Cigarette smoking is detrimental to health and linked to adverse health outcomes, including lung and other cancers, 45 47 asthma, 48 chronic obstructive pulmonary disease, 48 autoimmune diseases, 49 and adverse fertility outcomes in women 50 and men, 51 both in smokers themselves and those exposed to secondhand smoke. Cigarette smoking is associated with deleterious effects on ovarian steroidogenesis and gametogenesis, oocyte maturity, ovulation, fertilization, and implantation.…”
Section: Cigarette Smoking In Pregnancy: Known Risks To Fetal Health mentioning
confidence: 99%
“…Cigarette smoking is detrimental to health and linked to adverse health outcomes, including lung and other cancers, 45 47 asthma, 48 chronic obstructive pulmonary disease, 48 autoimmune diseases, 49 and adverse fertility outcomes in women 50 and men, 51 both in smokers themselves and those exposed to secondhand smoke. Cigarette smoking is associated with deleterious effects on ovarian steroidogenesis and gametogenesis, oocyte maturity, ovulation, fertilization, and implantation.…”
Section: Cigarette Smoking In Pregnancy: Known Risks To Fetal Health mentioning
confidence: 99%
“…In Australia, a study of practice nurse-delivered smoking cessation, including the offer of free nicotine patches, found a continuous abstinence rate of 16% (22% using point prevalence) after 6 months [29]. In Greece, a study on smokers with COPD and asthma found a 6 month continuous abstinence rate of 28.9% in smokers with COPD [30]. Compared in a Danish context results from the Danish Smoking Cessation Database primarily covering the smoking cessation activity in the municipalities showed an overall 6 month quit rate of 27% (ITT) using data from the period 2006e2011 [9], and an overall 12 month quit rate of 18% using data from the period 2001e2002 [10].…”
Section: Bi-variate Predictor Analysesmentioning
confidence: 99%
“…However, long-term follow-up of smoking cessation activities is in general rather effective in Denmark -both in the GP setting as well as in the municipality smoking cessation clinics setting e resulting in low drop-out rates. For comparison the Danish Smoking Cessation Database covering the smoking cessation activity of the municipality smoking cessation clinics did in 2013 reported a 16% drop-out rate at the 6 month follow-up for smokers included and following the clinics' 3-month quit program [30]. Repeated telephone calls to the participants (up to four times with one of them being in the evening) is the explanation to this low drop-out rate at 6 month followup from Danish smoking cessation activities.…”
Section: Bi-variate Predictor Analysesmentioning
confidence: 99%
“…In a retrospective, observational study, Gratziou and colleagues reported that the prevalence of depression among COPD patients with severe airway obstruction (FEV 1  < 50%) was 25% and they had a 2.5 times greater risk of depression in comparison to healthy smokers [7]. High prevalence of depression is independently associated with smoking [8] and failure to quit [9].…”
Section: Introductionmentioning
confidence: 99%